Refractory pituitary adenoma: a novel classification for pituitary tumors - Dai, Congxin (Oncotarget, 2016)
Pituitary adenomas are classified as typical or atypical, invasive or noninvasive, and aggressive or nonaggressive based on pathological features, radiological findings, and clinical behavior. Only pituitary tumors with cerebrospinal and/or systemic metastasis are considered malignant carcinomas. However, some pituitary adenomas with high Ki-67 indexes exhibit aggressive behaviors, such as rapid growth, early and frequent recurrence, and resistance to conventional treatment, even in the absence of metastasis. Novel terminology is needed to define these tumors. Here, we propose the use of the term “refractory pituitary adenoma” to define malignant pituitary tumors exhibiting 1) a high Ki-67 index and rapid growth, 2) early and high frequency of recurrence, 3) resistance to conventional treatments and/or salvage treatment with temozolomide (TMZ), 4) poor prognosis, 5) and a lack of cerebrospinal or systemic metastases. To illustrate the utility of this refractory pituitary adenoma classification and the difficulty in managing disease in these patients, we examined twelve clinical cases. Correctly identifying refractory pituitary adenomas is crucial for improving patient prognoses. Early identification might encourage the early use of aggressive therapeutic strategies to prevent or delay recurrence.